2016
DOI: 10.1002/ptr.5752
|View full text |Cite
|
Sign up to set email alerts
|

Side-Effects of Irinotecan (CPT-11), the Clinically Used Drug for Colon Cancer Therapy, Are Eliminated in Experimental Animals Treated with Latex Proteins fromCalotropis procera(Apocynaceae)

Abstract: Intestinal mucositis (IM) is the critical side effect of irinotecan (CPT-11), which is the front-line drug used for the treatment of colorectal cancer. This study aimed to evaluate the effectiveness of latex proteins (LP) from Calotropis procera to prevent IM and diarrhea in animals. Swiss mice were treated daily with saline or LP (1, 5, or 50 mg/kg, i.v.) 24 h prior to CTP-11 (75 mg/kg/4 days, i.p) and for additional 6 days. Animal survival, body weight variation, and diarrhea were registered. After animal sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…The COX-2 plays a key role in inflammation through the release of arachidonic acid, and biosynthesis of eicosanoids, such as prostaglandins involved in various immune and inflammatory responses. Several studies have demonstrated the harmful effect of radiotherapeutic and chemotherapeutic agents, which result in COX-2 overexpression in intestinal mucositis models [48,[65][66][67][68]. Hence, the anti-inflammatory effect of TRX on intestinal mucositis can be attributed to its binding and interaction with COX-2 and mediation of COX-2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The COX-2 plays a key role in inflammation through the release of arachidonic acid, and biosynthesis of eicosanoids, such as prostaglandins involved in various immune and inflammatory responses. Several studies have demonstrated the harmful effect of radiotherapeutic and chemotherapeutic agents, which result in COX-2 overexpression in intestinal mucositis models [48,[65][66][67][68]. Hence, the anti-inflammatory effect of TRX on intestinal mucositis can be attributed to its binding and interaction with COX-2 and mediation of COX-2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…(Santos‐Filho et al, ), Bidens pilosa L . (Bastos et al, ), wheat bran arabinoxylan supplementation (SONG et al, 2016), Colotropis procera (de Alencar et al, ), silymarin (Elyasi, Hosseini, Niazi Moghadam, Aledavood, & Karimi, ), and the herbal preparation Bu‐Zhong‐Yi‐Qi (Gou, Gu, Xiong, & Wang, ). In agreements, the management of chemotherapy‐induced nausea and vomiting has been achieved using traditional plant‐based medicines (Chen, May, Zhou, Zhang, & Xue, ), placing natural products as a potential source to alternative therapy to minimize chemotherapy side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Water soluble proteins extracted from the latex of C. procera Ait.Br. (Asclepiadaceae) have been demonstrated to alleviate arthritis and oxidative stress (Chaudhary et al, ; Chaudhary et al, ) and prevent oral and intestinal mucositis that result from chemotherapy (Alencar et al, ; Freitas et al, ). When incorporated into a biomembrane of polyvinyl alcohol, latex proteins have been found to accelerate the healing of incisional and excisional wounds (Figueiredo et al, ; Ramos et al, ).…”
Section: Introductionmentioning
confidence: 99%